Spaces:
Running
Running
Update app.py
Browse files
app.py
CHANGED
@@ -79,6 +79,12 @@ def calculate_probabilities(A, B, C, AB, AC, BC, ABC, U):
|
|
79 |
P_B_given_C_bayes = (PC_given_B * P_B) / P_C if P_C > 0 else 0
|
80 |
P_C_given_B_bayes = (PB_given_C * P_C) / P_B if P_B > 0 else 0
|
81 |
|
|
|
|
|
|
|
|
|
|
|
|
|
82 |
formatted_probs = {
|
83 |
"P(A)": f"{P_A:.2%} ({A}/{total})",
|
84 |
"P(B)": f"{P_B:.2%} ({B}/{total})",
|
@@ -99,6 +105,10 @@ def calculate_probabilities(A, B, C, AB, AC, BC, ABC, U):
|
|
99 |
"P(B | A) (T. Bayes)": f"{P_B_given_A_bayes:.2%} (Teorema de Bayes: (P(A | B) * P(B)) / P(A)) = ({PA_given_B:.4f} * {P_B:.4f} / {P_A:.4f})",
|
100 |
"P(C | A) (T. Bayes)": f"{P_C_given_A_bayes:.2%} (Teorema de Bayes: (P(A | C) * P(C)) / P(A)) = ({PA_given_C:.4f} * {P_C:.4f} / {P_A:.4f})",
|
101 |
"P(C | B) (T. Bayes)": f"{P_C_given_B_bayes:.2%} (Teorema de Bayes: (P(B | C) * P(C)) / P(B)) = ({PB_given_C:.4f} * {P_C:.4f} / {P_B:.4f})",
|
|
|
|
|
|
|
|
|
102 |
"U (Universal Set)": total,
|
103 |
"Complemento de A U B U C": U - (A + B + C - AB - AC - BC + ABC)
|
104 |
}
|
|
|
79 |
P_B_given_C_bayes = (PC_given_B * P_B) / P_C if P_C > 0 else 0
|
80 |
P_C_given_B_bayes = (PB_given_C * P_C) / P_B if P_B > 0 else 0
|
81 |
|
82 |
+
# Probabilidades de uniones
|
83 |
+
P_A_union_B = P_A + P_B - P_AB
|
84 |
+
P_A_union_C = P_A + P_C - P_AC
|
85 |
+
P_B_union_C = P_B + P_C - P_BC
|
86 |
+
P_A_union_B_union_C = ( P_A + P_B + P_C - P_AB - P_AC - P_BC + P_ABC )
|
87 |
+
|
88 |
formatted_probs = {
|
89 |
"P(A)": f"{P_A:.2%} ({A}/{total})",
|
90 |
"P(B)": f"{P_B:.2%} ({B}/{total})",
|
|
|
105 |
"P(B | A) (T. Bayes)": f"{P_B_given_A_bayes:.2%} (Teorema de Bayes: (P(A | B) * P(B)) / P(A)) = ({PA_given_B:.4f} * {P_B:.4f} / {P_A:.4f})",
|
106 |
"P(C | A) (T. Bayes)": f"{P_C_given_A_bayes:.2%} (Teorema de Bayes: (P(A | C) * P(C)) / P(A)) = ({PA_given_C:.4f} * {P_C:.4f} / {P_A:.4f})",
|
107 |
"P(C | B) (T. Bayes)": f"{P_C_given_B_bayes:.2%} (Teorema de Bayes: (P(B | C) * P(C)) / P(B)) = ({PB_given_C:.4f} * {P_C:.4f} / {P_B:.4f})",
|
108 |
+
"P(A ∪ B)": f"{P_A_union_B:.2%} (P(A) + P(B) - P(A ∩ B)) = ({P_A:.4f} + {P_B:.4f} - {P_AB:.4f})",
|
109 |
+
"P(A ∪ C)": f"{P_A_union_C:.2%} (P(A) + P(C) - P(A ∩ C)) = ({P_A:.4f} + {P_C:.4f} - {P_AC:.4f})",
|
110 |
+
"P(B ∪ C)": f"{P_B_union_C:.2%} (P(B) + P(C) - P(B ∩ C)) = ({P_B:.4f} + {P_C:.4f} - {P_BC:.4f})",
|
111 |
+
- "P(A ∪ B ∪ C)": f"{P_A_union_B_union_C:.2%} (P(A) + P(B) + P(C) - P(A ∩ B) - P(A ∩ C) - P(B ∩ C) + P(A ∩ B ∩ C)) = ({P_A:.4f} + {P_B:.4f} + {P_C:.4f} - {P_AB:.4f} - {P_AC:.4f} - {P_BC:.4f} + {P_ABC:.4f})",
|
112 |
"U (Universal Set)": total,
|
113 |
"Complemento de A U B U C": U - (A + B + C - AB - AC - BC + ABC)
|
114 |
}
|